KORELASI ASPEK PSIKOLOGI DAN PERAN TENAGA KESEHATAN DALAM PEMBERIAN ASI EKSLUSIF - Blongkod, Fitriani Rahmatismi; Suyati, Suyati; Sulistyowati, Endang; Wirawan, Susilo (Ensiklopedia of Journal, 2024)
Abstract: Breast milk is a very important source of nutrition and has a balanced composition to support optimal growth and development of infants. According to data obtained at various clinics in Central Tapanuli District, there is a significant difference in formula feeding based on the age of the mother. As many as 47% of mothers over 30 years old and 31% of mothers under 18 years old choose to give formula milk to their children. The purpose of the study was to determine the correlation between psychological aspects and the role of health workers in exclusive breastfeeding. The research design used in this study was cross sectional. The research was conducted in January 2024 at 5 clinics in Central Tapanuli Regency. The population was mothers who gave birth who made postnatal visits totaling 165 people. The sample amounted to 61 people. The sampling technique used simple random sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between psychological aspects (p value: 0.001) and the role of health workers (p value: 0.006) with exclusive breastfeeding. It is recommended that health workers increase support and motivation for exclusive breastfeeding even though mothers work.Keywords: Exclusive Breastfeeding, Psychology, Health Workers